"influencia de la dosificación del mucilago del linum usitatissimun sobre la velocidad de corrosión del acero astm a335 p11 en hcl 0.5 m, a diferentes temperaturas” - Chirinos Alcántara, Ángel Enrique (2016)
The inhibition of the corrosion of the steel ASTM A335 grade P11 in 0.5 M hydrochloric acid at temperature different, by the flaxseed mucilage, was investigated using techniques: Tafel extrapolation, electrochemical impedance spectroscopy and electrochemical frequency modulation. The flaxseed mucilage acts as an optimum corrosion inhibitor of the P11 steel in HCl. The efficiencies of inhibition obtained were of 85.7% at 25 oC, 93.6% at 45 oC and 96.3% at 65 °C, a concentration of the mucilage of 1 g/l. In both steels it was found that the efficiency of inhibition, the adsorption constant and the standard free energy of adsorption increased with increasing temperature. The standard enthalpy of adsorption was positive and the apparent activation energy decreased with the increase of the concentration of the mucilage. All these parameters indicate that the adsorption of flaxseed mucilage in steels evaluated occurs through a chemical adsorption. In addition, the mucilage acts as an inhibitor of mixed type. Keywords: flaxseed mucilage, hydrochloric acid, corrosion rate, acid inhibition, adsorption, ASTM A335 P11 steel, electrochemical techniques, EIS, EFM.